Examining the Factors Affecting Firm Values : The Case of Listed Manufacturing Companies In Indonesia - Diana, Erika (Universitas Syiah Kuala, 2020)
Objective This study aims to examine the effect of cash holding, earnings management, profitability, company size, and financial leverage on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Design/methodology This study used hypothesis testing. Samples were selected using purposive sampling as many as 82 companies. Data obtained from annual reports and analyzed using panel data regression analysis method. Results The results showed that cash holding, earnings management, and profitability as inde-pendent variables, company size and financial leverage as control variables jointly affect the value of the company. Partially, earnings management has no effect on firm value, while cash holding, profitability, company size, and financial leverage have an effect on firm value.